Changes in primary and secondary hemostasis in patients with CLL treated with venetoclax and ibrutinib. Issue 14 (5th December 2020) - Svanberg, Rebecka; Ostrowski, Sisse Rye; Nasserinejad, Kazem; Kersting, Sabina; Dobber, Johan A.; Mattson, Mattias; Tran, Hoa T. T.; Levin, Mark-David; Mous, Rogier; Kater, Arnon P.; Niemann, Carsten U.
Abstract: Bleeding is a common adverse event following ibrutinib monotherapy. However, it remains unclear how hemostasis is affected by venetoclax in combination with ibrutinib. Here we investigated hemostasis in patients with chronic lymphocytic leukemia (CLL) at baseline, during ibrutinib monotherapy, and during venetoclax and ibrutinib combination therapy or venetoclax monotherapy. Primary hemostasis, assessed by Multiplate using adenosine diphosphate (ADP), arachidonic acid (AA), and thrombin receptor agonist peptide (TRAP-6), was impaired in all CLL patients at baseline, remained unchanged upon ibrutinib monotherapy, and improved significantly following venetoclax added to ibrutinib or as monotherapy. Secondary hemostasis assessed by thromboelastography (TEG) was normal and unchanged throughout treatment. The frequency of clinical bleeding events was the highest during ibrutinib monotherapy, in line with the demonstrated improved primary hemostasis upon addition of venetoclax, thus pointing toward a treatment option for CLL patients with increased bleeding risk.